Fabrication and real time testing of a tilt-rotor tricopter - Brian, Kenny (2017)
In recent years, there has been an increasing interest in the development of lightweight and small sized unmanned aerial vehicles as technology continues to disrupt industries worldwide. Non-conventional platforms, such as tricopters, are also gaining popularity due to their superior manoeuvrability and higher cruising speeds. In this project, various manufacturing techniques are used to produce a tilt-rotor tricopter that is small and lightweight. Two tricopter prototypes are manufactured using diﬀerent techniques. One was 3D printed using ABSplus as its ﬁlament. Assembly and fabrication challenges lead to several design modiﬁcations to the second prototype, which is 3D printed and reinforced with carbon ﬁbre prepregs, increasing the structure’s stiﬀness and strength. The ﬁnal prototype weighs 14% lighter and is 25 % smaller in size than the original platform. It will eventually be used to perform various control experiments in a motion capture laboratory. Models of the tricopter are created using Solidworks in order to test closed loop control algorithms in a simulated environment. Upon successful simulation of the control algorithm, the tricopter is tested in real-time. The structure proved to be robust and lighter while demonstrating satisfactory response to trajectory commands. Based on the test results, it is concluded that carbon ﬁbre reinforcements may not be an ideal technique to be used in conjunction with rapid prototyping. In addition, smaller tricopter designs can be achieved with the use of lighter batteries, which reduces the overall weight and, in turn, the size of propellers used as well. Recommendations for future development of the tricopter are explored further in the report.